Quadrature Rule Based Iterative Method for the Solution of Non-Linear Equations: Quadrature Rule for the Solution of Non-Linear Equations - Qureshi, Umair Khalid; Bozdar, Irfan Ali; Pirzada, Aliya; Arain, Muzaffar Bashir (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This research has suggested a quadrature rule based iterative method for the solution of non-linear algebraic and transcendental equations. The proposed iterated method is derived from Quadrature Formula and Numerical Technique. The quadrature rule based iterative method is converged quadratically, and it is free from pitfall. Few of physical non-linear problems to demonstrate the competency of proposed iterative method with the assessment of Steffensen Method and Newton Raphson Method. C++ and EXCEL have been used to examine the numerical results and graphical illustration of quadrature rule based iterative method. Hence, from several examples illustrate that the convergence and efficiency of the quadrature rule based iterative method is better than Steffensen Method and Newton Raphson Method.